(untitled) (Research, Society and Development, 2022)
In the teaching and learning process, the phonic method has become a much discussed subject within education, being a method for the literacy and literacy process, since it has skills capable of preparing the student to develop the necessary skills in the short term, compared to the other methods. The objective of this study was to understand the importance of including the phonic method as an efficient process for literacy and literacy, as well as the acceptance by educational institutions and teachers in its implementation in the literacy cycle. This is a bibliographic research, based on scientific publications from the use of the combination of keywords in Google Scholar, SciElo, scientific websites, educational laws and books. The results were discussed in an argumentative critical text and analyzed qualitatively. The use of the phonic method as an educational tool is considered a solution to overcome the deficit in literacy and literacy of many children, expanding their learning possibilities and the development of various metalinguistic skills, such as phonological awareness and its units. The study of this teaching method will serve as guidance to teachers in the applicability of their methodologies and analysis of their effectiveness. Therefore, the question raised is of total relevance, since it refers to a promising study that aims to bring important advances to Brazilian education.